Nitrogen fertilization, baseline and projections of greenhouse gases in Colombia - Torres, Carlos Felipe (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The workshop on emissions from the use of nitrogen fertilizers, baseline and greenhouse gas (GHG) projections in Colombia includes among its objectives the strengthening of the development of greenhouse gas inventories in the country through the improvement of the N2O estimates of the soil associated with nitrogen fertilizers applied in the different crop systems. In addition, the project seeks to consolidate the use of the results of the research generated to strengthen public policies such as the Nationally Determined Contribution (NDC), the Colombian Low Carbon Development Strategy (ECDBC) and the sector mitigation plan.